TINJAUAN YURIDIS TERHADAP PENJATUHAN SANKSI PIDANA PADA ANAK PELAKU PENGANIAYAAN BERAT YANG MENYEBABKAN KEMATIAN (STUDI PUTUSAN NOMOR 12/Pid.Sus-Anak/2020/PN Jkt.Pst) - Dicky Darmawi; Diding Rahmat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
This study aims to analyze the juridical considerations of the panel of judges in imposing criminal sanctions on a child perpetrator of aggravated assault that resulted in death, as reflected in Decision Number 12/Pid.Sus-Anak/2020/PN Jkt.Pst. This research uses a normative juridical method with a statutory and case study approach. The findings indicate that the judges applied the principle of lex specialis derogat legi generali, prioritizing the Child Protection Act and the Juvenile Criminal Justice System Act (UU SPPA) over the general provisions of the Indonesian Penal Code (KUHP). Under the old Penal Code, aggravated assault resulting in death is regulated in Article 351 paragraph (3) with a maximum sentence of 7 years, while the new Penal Code, stipulated in Law Number 1 of 2023, regulates the same offense in Article 354 paragraph (3), with a maximum sentence of 12 years. In contrast, the Child Protection Act (Article 80 paragraph (3)) prescribes up to 15 years imprisonment. However, since the perpetrator is a child, Article 81 of the Juvenile Criminal Justice System Act limits the maximum sentence to half, which is 7.5 years. The judge also rejected the application of diversion due to the threat of imprisonment exceeding 7 years, in accordance with Article 7 paragraph (2) of the SPPA Law. Based on considerations of the perpetrator’s age (14 years), psychological condition, family background, and rehabilitative recommendations from BRSAMPK Handayani, the court imposed a two-year educational sanction at a Social Welfare Institution (LPKS). Although the verdict received criticism for being too lenient, the judge took into account child protection principles, the ultimum remedium principle, and the best interests of the child. This decision reflects a juvenile justice paradigm that emphasizes educational and restorative approaches rather than mere punishment.